European Economic Governance and Parliamentary Representation. What Place for the European Parliament?. Issue 2 (1st August 2013) - Fasone, Cristina
Abstract This article aims to analyse the European Parliament's (EP) position in the reform of the European economic governance, in particular after the adoption of the 'six‐pack, ' the 'two‐pack' and the 'fiscal compact.' References are made to the involvement of the EP in the decision‐making process that led to the adoption of the new measures as well as to the substantive role assigned to this institution in the new regulatory framework. The article argues that the new provisions, which undermine the budgetary authority of national parliaments while, at the same time, designing a limited role for the EP—though strengthened compared to the previous version of the Stability and Growth Pact—can jeopardise the effectiveness of the landmark principle of 'no taxation without parliamentary representation' in the EU.